2014
DOI: 10.1038/am.2014.98
|View full text |Cite|
|
Sign up to set email alerts
|

Amorphous iron phosphate: potential host for various charge carrier ions

Abstract: In response to the ever-increasing global demand for viable energy-storage systems, sodium and potassium batteries appear to be promising alternatives to lithium ion batteries because of the abundance, low cost and environmental benignity of sodium/ potassium. Electrical energy storage via ion-intercalation reactions in crystalline electrodes is critically dependent on the sizes of the guest ions. Herein, we report on the use of a porous amorphous iron phosphate synthesized using ambient temperature strategies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
151
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(157 citation statements)
references
References 40 publications
2
151
0
1
Order By: Relevance
“…Therefore, nanosized amorphous materials should have better cycling performance during the discharge/charge process than bulk crystalline ones. In addition, the high level of disorder in amorphous materials decreases charge transport resistance [10] and enhances the ability to host charge carrier ions [95], the latter of which is illustrated in Fig. 12.…”
Section: Applications Electrochemical Electrode Materialsmentioning
confidence: 99%
“…Therefore, nanosized amorphous materials should have better cycling performance during the discharge/charge process than bulk crystalline ones. In addition, the high level of disorder in amorphous materials decreases charge transport resistance [10] and enhances the ability to host charge carrier ions [95], the latter of which is illustrated in Fig. 12.…”
Section: Applications Electrochemical Electrode Materialsmentioning
confidence: 99%
“…[6][7][8] Amorphous iron phosphates have been identified as a promising cathode material for SIBs in view of their unique properties. Compared with its crystalline counterpart, the amorphous framework of FePO 4 is defect free, can provide more available sites for Na ions and can exhibit less structural confinement to the reversible insertion/extraction for Na ions, [9][10][11] which ensure a much improved structural stability over long-term cycling. Unfortunately, iron phosphates themselves are well known for their poor electronic conductivity, 12,13 leading to sluggish electron transport during cycling, which becomes a critical issue in the consideration of FePO 4 as a practical cathode material.…”
Section: Introductionmentioning
confidence: 99%
“…18 From 2012 on, other studies reported the performance of different active materials (amorphous FePO 4 , FeSO 4 F, carbon nanofibers, organic electrode) in potassium-metal cells and with different organic electrolytes. [19][20][21][22] The use of K metal is not likely to be accepted for a practical application due to severe safety concerns, which are undoubtedly higher than for Li or even Na metal. For this reason, interest lies in finding suitable anode materials which can be applicable in K-ion full cells, thus reducing the risks associated with K metal.…”
mentioning
confidence: 99%